2023
DOI: 10.1097/hjh.0000000000003433
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between measures of adiposity, blood pressure and arterial stiffness in adolescents. The MACISTE study

Abstract: Objective:Children and adolescents with adiposity excess are at increased risk of future cardiovascular (CV) disease. Fat accumulation promotes the development of elevated blood pressure (BP) and arterial stiffness, two main determinants of CV risk which are strongly inter-related. We aimed at investigating whether the association between overweight and arterial stiffness, taken at different arterial segments, is mediated by increased BP or is BP-independent.Methods:Three hundred and twenty-two Italian healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
2
1
Order By: Relevance
“…Some authors have also suggested that in obese adolescents, there is an inverse correlation between cf-PWV and BMI values. On the other hand, several studies show a close relationship between insulin resistance and arterial stiffness in children and adolescents [44,[47][48][49], and this suggests that excess weight and visceral fat (related to insulin resistance) may be associated with different effects on arterial viscoelasticity, although not all authors agree on this point [50]. Our study did not show an association between cf-PWV and BMI.…”
Section: Aortic Pulse Wave Velocitycontrasting
confidence: 74%
See 1 more Smart Citation
“…Some authors have also suggested that in obese adolescents, there is an inverse correlation between cf-PWV and BMI values. On the other hand, several studies show a close relationship between insulin resistance and arterial stiffness in children and adolescents [44,[47][48][49], and this suggests that excess weight and visceral fat (related to insulin resistance) may be associated with different effects on arterial viscoelasticity, although not all authors agree on this point [50]. Our study did not show an association between cf-PWV and BMI.…”
Section: Aortic Pulse Wave Velocitycontrasting
confidence: 74%
“…There is no agreement in the literature regarding the relationship between BMI and vascular stiffness in children and adolescents. Some data suggest that there is no influence of excess weight on cf-PWV [33,44], while others go in the opposite direction [45,46]. Some authors have also suggested that in obese adolescents, there is an inverse correlation between cf-PWV and BMI values.…”
Section: Aortic Pulse Wave Velocitymentioning
confidence: 99%
“…We applaud the efforts of Pucci et al . [1] in their research titled ‘Adiposity and Arterial Stiffness in Healthy Adolescents: Exploring Blood Pressure Mediation’. Interestingly, the findings reveal a stronger association between neck circumference and carotid stiffness than aortic stiffness, independent of blood pressure (BP).…”
mentioning
confidence: 99%